Seismo-Stratigraphic Model for the Urban Area of Milan (Italy) by Ambient-Vibration Monitoring and Implications for Seismic Site Effects Assessment - Massa, M.; Lovati, S.; Puglia, R.; Brunelli, G.; Lorenzetti, A.; Mascandola, C.; Felicetta, C.; Pacor, F.; Luzi, L. (Frontiers in Earth Science, 2022)
In this paper, we present the work carried out to characterize the spatial variability of seismic site response related to local soil conditions in the city of Milan and its surroundings, an area with ~ 3 million inhabitants and a high density of industrial facilities. The area is located at the northwestern end of the Po Plain, a large and deep sedimentary basin in northern Italy. An urban-scale seismo-stratigraphic model is developed based on new passive and active seismic data, supported by the available geological data and stratigraphic information from shallow and deep vertical wells. In particular, 33 single-station and 4 ambient-vibration array measurements are acquired, together with 4 active multichannel analyses of surface waves (MAWS). To estimate the resonant frequencies of the sediments, the horizontal to vertical spectral ratio technique (HVSR) is applied to the ambient-vibration recordings, whereas to determine the Rayleigh-wave dispersion curves from the passive array, the data are analysed using the conventional frequency-wavenumber, the modified spatial autocorrelation and the extended spatial autocorrelation (ESAC) techniques. The array data are used to determine the local shear wave velocity profiles, VS, via joint inversion of the Rayleigh-wave dispersion and ellipticity curves deduced from the HVSR. The results from HVSR show three main bands of amplified frequencies, the first in the range 0.17-0.23 Hz, the second from 0.45 Hz to 0.65 Hz and the third from 3 Hz to 8 Hz. A decreasing trend of the main peaks is observed from the northern to the southern part of the city, allowing us to hypothesize a progressive deepening of the relative regional chrono-stratigraphic unconformities. The passive ambient noise array and MASW highlight the dispersion of the fundamental mode of the Rayleigh-wave in the range 0.4-30 Hz, enabling to obtain detailed Vs profiles with depth down to about 1.8 km. The seismo-stratigraphic model is used as input for 1D numerical modelling assuming linear soil conditions. The theoretical 1D transfer functions are compared to the HVSR curves evaluated from both ambient noise signals and earthquake waveforms recorded by the IV.MILN station in the last 10 years.